Transaksi E-Commerce dalam Perspektif Hukum Ekonomi Syariah - Muhammad Razi Al Faruqi; Rusdiana Priatna Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the validity of e-commerce contracts under Islamic Sharia law, focusing on applying traditional contract principles to digital transactions. Employing a qualitative descriptive approach, data were gathered through a literature review, expert interviews, and analysis of online platform terms and conditions. Interactive data analysis was used to understand the contractual challenges comprehensively. The findings reveal inconsistencies between standard e-commerce practices and Sharia requirements for valid contracts, particularly regarding ijab (offer), qabul (acceptance), and the clarity of contractual terms. The research emphasizes the importance of transparency, mutual agreement, and avoiding gharar (uncertainty) in ensuring sharia-compliant transactions. This study contributes a conceptual framework for adapting Sharia contract principles to the digital environment, offering practical guidance for regulators, digital businesses, and legal scholars. By proposing a model for Sharia-compliant e-commerce contracts, the research promotes a more ethical and inclusive digital marketplace.